T cell Allorecognition Pathways in Solid Organ Transplantation - Siu, Jacqueline H. Y.; Surendrakumar, Veena; Richards, James A.; Pettigrew, Gavin J. (Frontiers in Immunology, 2018)
Transplantation is unusual in that T cells can recognize alloantigen by at least two distinct pathways: as intact MHC alloantigen on the surface of donor cells via the direct pathway; and as self-restricted processed alloantigen via the indirect pathway. Direct pathway responses are viewed as strong but short-lived and hence responsible for acute rejection, whereas indirect pathway responses are typically thought to be much longer lasting and mediate the progression of chronic rejection. However, this is based on surprisingly scant experimental evidence, and the recent demonstration that MHC alloantigen can be re-presented intact on recipient dendritic cells – the semi-direct pathway – suggests that the conventional view may be an oversimplification. We review recent advances in our understanding of how the different T cell allorecognition pathways are triggered, consider how this generates effector alloantibody and cytotoxic CD8 T cell alloresponses and assess how these responses contribute to early and late allograft rejection. We further discuss how this knowledge may inform development of cellular and pharmacological therapies that aim to improve transplant outcomes, with focus on the use of induced regulatory T cells with indirect allospecificity and on the development of immunometabolic strategies.